A Cultural Account of Ecological Democracy. (1st February 2019) - Hammond, Marit
In the debate around ecological democracy, a pivotal point of contention has long been the question why democracy should actually be expected, as some claim, to deliver (more) ecological outcomes. This point is empirical as well as conceptual: it is difficult to conceive why voters would support any policies that - as is often (perceived to be) the case with environmental legislation - would leave them worse off; whilst democracy conceptually must remain open to all outcomes rather than being tied to any particular agenda ex ante. Yet both empirically and conceptually, the nature and extent of this key puzzle has always hinged on the particular definitions used. This paper reconsiders the link between democracy and ecological sustainability from a cultural angle: I argue that conceiving of both sustainability and democratisation as essentially cultural transformations resolves the puzzle and thus makes a renewed case for ecological democracy. Only as cultural processes - the creation of new meanings of sustainable prosperity in people's everyday lives, and a culturally rather than institutionally based form of democratisation - can these transformations be deep-seated rather than superficial, and thus self-perpetuating rather than merely enforced.